أثر قناة طيور الجنة على الصحة النفسية للأطفال من وجهة نظر الأخصائيين النفسانيين - عدائكة, عبد الله (University of Eloued جامعة الوادي, 2017)
هدفت هذه الدراسة إلى التعرف على أثر قناة طيور الجنة على الصحة النفسية للأطفال من وجهة نظر الاخصائيين النفسانيين حيث اتبع الباحث المنهج الوصفي، وقد تكونت عينة الدراسة من 49 أخصائية وأخصائي نفساني على مستوى ولاية الوادي كجمعية التاج للتوحد بقمار وجمعية التوحد بطريق تقرت، ومركز خطوة لتطوير القدرات العقلية قرب الولاية القديمة، وأغلب المختصين بالقطاع العمومي والخاص. وقد أجريت خمس مقابلات مع الأمهات والآباء المصابين أبنائهم كانوا مدمنين على قناة طيور الجنة. وكذا اعتمدنا على الملاحظة المباشرة على سلوكات الأطفال الذين كانوا مدمنين على مشاهدة قناة طيور الجنة وهم الآن في فترة المعالجة. وقد أظهرت نتائج الدراسة ان أغلبية الأطفال مع أنهم كانوا طبيعيين في الأشهر الأولى باتوا يعانون من مشكلات على مستوى الاتزان العاطفي، وخلل في الوظائف العقلية، وكذا مشكلات على مستوى التكيف الاجتماعي والتفاعل أغلبها بسبب عدم التواصل مع الطفل وهذا يظهر جليا في تركه لساعات طويلة أمام التلفاز خاصة أمام قناة طيور الجنة بحكم أنها الاقدر على التأثير لما تتميز به من كثرة الألوان والحركة، والصورة والجاذبية، والموسيقى. This study has aimed us to know the effect of Touyour El-djannah channel on kid’s psycholigical health from specialized psychologists point of vue where the researcher has followed the discriptive method a sample of study composed of 49 specialists and psycholological specialist on the level of the state of El Oued as Tadj association for autism in Guemar and autism association in Touggourt road, and the center khotwa for developing mental capacities near to the old state and most the specialists on public and private sector. Five interviews have been done with mothers and fathers that their kids were addicted to Toyor El Djennah channel, and we depended on the direct observation of children’s behaviours that were addicted to watching Toyour El Djennah channel and now are on the treatment period. The study results have showthat most of children even though they were normal on the first months, now, they are suffering from issues on the level of emotional balance, a disfunction in mental functions and problems on the social adaptation and interaction, most of them are because of the lack of communication with the child and that is obvious when leaving him in front of TV for hours especially Toyour El Djennah depending on the fact that it’s able to effect on what it is characterized of lot of colors and action, image gravity and music, so that children find what they were looking for and acquires all their minds and they shall heal their sorrows.
مذكرة ماستر تخصص دعوة واعلام
Keywords: قناة، الأطفال، الاخصائيين النفسانيين, Channel children ، Psychologists